PERSEPSI SISWA TERHADAP KOMPETENSI PROFESIONALISME GURU KEAHLIAN JASA BOGA SMK NEGERI 1 PAINAN - Rahmawati, Intan; Yusuf, Liswarti; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The purpose of this for study was to identify and describe how students perceptionts of teacher professional competence skills catering services SMK Negeri 1 Painan. This resereach is quantitative descriptive. The populations consist 0f 90 people namely grate students X, XI, and XII SMK Negeri 1 Painan. Based on the result of this study concluded that: 35% of respondents had the perception that the teacher is good mastery of the material, 33% of respondents had the perception that the teacher is good management of teaching and learning, 42% of respondents had the perception that the teacher is good classroom management and workshop, 43% of respondents had the perception that the teacher use of media to learn good teacher, 45% of respondents had the perception that the teacher the management of teaching and learnings interactions, and 43% of respondents had the perception that the teacher is good evaluation of learning achievement. The result showed that overall 43% of respondents students perceptions of teacher professional competence is very good category. Â Keywords: perception, teacher professional competence